Att bygga för lönsamhet - Andersson, Kristoffer (2005)
I have made a study about how the investment-calculation and the profitability looks when doing an extension from 50 to 120 cows on a farm in Småland. The reason for this choice of subject is that the specialist press have been writing a lot about the need to be able to build cheaper buildings. I have also been curious about how the statement of costs looks when building a cow-house with well-tried solutions. The purpose of this work is to find out how to increase the milk production on this farm to get the best profit. I have compared different systemsolutions in the storage of dung, handling of animal feed and ways of milking. I have got offer from several companies that have interesting products and then I have put them together in an investment calculation. To be able to understand the profitably of the three different buildings alternatives I have made a managmentplan for those alternatives. To invest in a used tower silo and automatic handling of the animal feed gives the best economy. A scientific research showed that it´s 20 öre more expensive to obtain one kg of milk with an VMS than with a milking-pitt. In my investmentcalculation the level of investments will be between 43000-56000 SEK /cow. When adding the additional investments outside the cow house the level of investment will be between 69000-83000 SEK/cow. The most profitable alternative will be a built cow-house for 140 cows with a milking-pitt.